PENGARUH LITERASI EKONOMI DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Henny Hendrawita; Caska Caska; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine: (1) the effect of economic literacy on the consumptive behavior of students of Economic Education FKIP Riau University; (2) the influence of lifestyle on the consumptive behavior of students of Economic Education FKIP Riau University; (3) the influence of economic literacy and lifestyle on the consumptive behavior of students of Economic Education FKIP, Riau University. The subjects in this study were students of Economic Education FKIP Riau University Class of 2017 and 2018 with a total sample of 61 people who were taken using simple random sampling technique. The research approach is a quantitative approach, while the data collection methods used are test questions and questionnaires. The data were analyzed using descriptive analysis and multiple linear regression. The results showed that: (1) Economic literacy has a positive and significant effect on the consumptive behavior of students of Economic Education FKIP, Riau University; (2) Lifestyle has a positive and significant effect on the consumptive behavior of students of Economic Education FKIP Riau University; (3) Economic literacy and lifestyle have a positive and significant effect on the consumptive behavior of students of Economic Education FKIP, Riau University.Key Words: Economic Literacy, Lifestyle, Consumptive Behavior